2014
DOI: 10.1038/aps.2014.36
|View full text |Cite
|
Sign up to set email alerts
|

Cell-based assays for Parkinson's disease using differentiated human LUHMES cells

Abstract: Aim: Lund human mesencephalic (LUHMES) cells can be differentiated to post-mitotic cells with biochemical, morphological and functional features of dopaminergic (DAergic) neurons. Given the limited scale of primary DAergic neuron culture, we developed differentiated LUHMES cell-based cytotoxicity assays for identifying neuroprotective agents for Parkinson's disease (PD). Methods: LUHMES cells were incubated in a differentiation medium containing cAMP and GDNF for 6 d, and then differentiated cells were treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 28 publications
1
53
1
Order By: Relevance
“…LUHMES cells are used as highly reproducible test system for neurotoxicity investigations or to model aspects of neurodegenerative disease (Delp et al 2017, 2018; Harris et al 2017; Krug et al 2014; Poltl et al 2012; Sarkar et al 2017; Schildknecht et al 2013; Scholz et al 2011; Stiegler et al 2011; Szego et al 2017; Xiang et al 2013; Zhang et al 2014). Since the MPP + model for Parkinson’s disease is frequently used by us and others (Schildknecht et al 2017; Terron et al 2018), the finding that the induction of cell death in LUHMES purchased from ATCC required 16 times higher concentration of the neurotoxicant MPP + (Zhang et al 2014), than found for the original cells (“UKN”) (Krug et al 2014; Poltl et al 2012; Schildknecht et al 2009), raised concerns about the definitions of cell line identity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LUHMES cells are used as highly reproducible test system for neurotoxicity investigations or to model aspects of neurodegenerative disease (Delp et al 2017, 2018; Harris et al 2017; Krug et al 2014; Poltl et al 2012; Sarkar et al 2017; Schildknecht et al 2013; Scholz et al 2011; Stiegler et al 2011; Szego et al 2017; Xiang et al 2013; Zhang et al 2014). Since the MPP + model for Parkinson’s disease is frequently used by us and others (Schildknecht et al 2017; Terron et al 2018), the finding that the induction of cell death in LUHMES purchased from ATCC required 16 times higher concentration of the neurotoxicant MPP + (Zhang et al 2014), than found for the original cells (“UKN”) (Krug et al 2014; Poltl et al 2012; Schildknecht et al 2009), raised concerns about the definitions of cell line identity.…”
Section: Discussionmentioning
confidence: 99%
“…Since the MPP + model for Parkinson’s disease is frequently used by us and others (Schildknecht et al 2017; Terron et al 2018), the finding that the induction of cell death in LUHMES purchased from ATCC required 16 times higher concentration of the neurotoxicant MPP + (Zhang et al 2014), than found for the original cells (“UKN”) (Krug et al 2014; Poltl et al 2012; Schildknecht et al 2009), raised concerns about the definitions of cell line identity. Even though we found here SP of LUHMES from different sources to be highly similar on the genomic level (same STR-profile; PI_HAT score ≈ 1), we identified clear phenotypic and toxicological differences using a targeted identity profiling.…”
Section: Discussionmentioning
confidence: 99%
“…For these studies, we used human mesencephalon-derived neuronal LUHMES cells, which are used to model human dopaminergic degeneration (53). With the addition of cAMP and GDNF, LUHMES cells differentiate by forming long axons with relatively dense interconnections typically seen in the mesencephalic region in the brain (54).…”
Section: Resultsmentioning
confidence: 99%
“…Despite increased sensitivity to the tested neurotoxicants, the MPP+ concentrations used in this study are quite high (100–1,000 uM) compared to the 5‐μM concentrations previously reported to induce significant (<50% intracellular ATP) LUHMES cell death . While previous studies used a 72‐h MPP+ exposure, 48‐h MPP+ exposure has been reported to have an LD50 of approximately 100 μM . Experiments also produced variable results with our neurotoxicant screen producing LC50 values similar to previous literature in one trial (Figure S3) while subsequent trials resulted in considerably higher LC50s.…”
Section: Discussionmentioning
confidence: 55%